Assessment of the Curricular Reform of a Medical Course from the Faculty’s Perspective - Pavan,Maria Valéria (2019)
ABSTRACT In 2006, the medical course of the Faculty of Medical Sciences and Health of PUC-SP (FCMS of PUC-SP) completely restructured its curriculum and pedagogical project and began to use active teaching/learning methods, centered on problem-based learning. There is often some resistance on the part of the teachers in relation to the changes, depending on the consequences for their daily practice. However, the participation of the teachers and their commitment to reform proposals are fundamental for them to occur and to be continually renewed. In this sense, this study had as objective to evaluate the teachers’ view of the FCMS of the PUC-SP medical course on the changes triggered by the curricular reform; the impact of these changes on their own work, on the quality of the course and on the graduate doctor and, the suggestions to improve the curriculum, as part of the ongoing goal to produce well-trained professionals adapted to the needs of the population and to the health care system. The data were obtained through a pre-tested semi-structured questionnaire, sent to the teachers working on the medical course. The second part of the questionnaire, object of this article, was to be answered only by the teachers who were already working before the curricular reform. Of the 178 teachers, 102 answered the questionnaire and, of these, 73 (71.6%) had already worked on the course before the curricular reform and answered the second part of the questionnaire. In general, the teachers have a positive view of the changes triggered by the reform, with emphasis on the active role of the student in the teaching/learning process and the growth provided to the teacher, induced by the pedagogical model chosen. They also consider that there has been an improvement in the quality of the course and the graduate doctor. Although well evaluated, the change to an interdisciplinary model and the deficiencies of the physical structure and equipment made available for the course complicate the work of the teacher. The difficulty in evaluating the student and the lack of a permanent teacher development plan appear as the main problems to be faced in the search for improving the course.